Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Audit Di Lingkungan Pemerintah Kabupaten/Kota Se-Eks Karesidenan Surakarta - Pujiastuti, Indah, Dr. Atwal Arifin, Akt, M.Si (2014)
This research has entitled "Analysis of Factors Which Affecting the Quality of Environmental Audit in Regency/Municipal throughout Ex Surakarta Residency". The goal of this research is to provide empirical evidence about the influence of the independence, objectivity, work experience, knowledge and integrity of auditors on audit quality in the Regency/Municipality throughout Ex Surakarta Residency. This research uses a quantitative approach. The data used in this research is primary data. In this research, the primary data used was a questionnaire that presented directly to the auditor or examiner staff who worked on the Inspectorate Office of the District/Municipal throughout Ex Surakarta. Data analysis tool used in this research is multiple linear regression analysis. The data collection technique used was survey method. The results of this research indicated that (1) The independence doesn't affect of audit quality, with a significance value of 0.104 > 0.01 (2) the objectivity affect of audit quality, with a significance value of 0.004 < 0.01 (3) work experience does not affect the quality audit, with a significance value 0.480 > 0.01 (4) knowledge has no effect on audit quality, with a significance value of 0.110 > 0.01 and (5) affect the integrity of audit quality, with a significance value of 0.000 < 0.01.